Hydrological modeling of sustainable land management interventions in the Mizewa watershed of the Blue Nile Basin - Schmidt, Emily; Zemadim, Birhanu (International Food Policy Research Institute, 2014)
This analysis utilizes recent hydrological and meteorological data collected from the Mizewa watershed in order to better understand the physical impact of SLWM investments. The effectiveness of the simulated conservation practices (terraces, bunds, and residue management) are evaluated using the Soil and Water Assessment Tool (SWAT) model taking into account investment decisions on different terrain types.